3D LiCoO2 nanosheets assembled nanorod arrays via confined dissolution-recrystallization for advanced aqueous lithium-ion batteries. (February 2019) - Xue, Liang; Zhang, Qinghua; Zhu, Xiaohui; Gu, Lin; Yue, Jili; Xia, Qiuying; Xing, Ting; Chen, Tingting; Yao, Yao; Xia, Hui
Abstract: Three-dimensional (3D) electrodes with freestanding feature represent the state-of-art electrode design for advanced lithium-ion batteries. Construction of 3D architectures for cathode materials, however, is still a great challenge. In this work, freestanding 3D LiCoO2 nanosheets assembled nanorod arrays are grown on carbon fabric via confined dissolution-recrystallization on the Co(CO3 )1-x (OH)2x ·nH2 O nanowire arrays during hydrothermal treatment. The formed intermediate CoOOH nanosheets can catalyze the decomposition of H2 O2 and the generated continuous oxygen bubble layer enables self-limiting dissolution-recrystallization. After final heat treatment at a low temperature of 380 °C, the obtained 3D hierarchy LiCoO2 nanorod arrays exhibit large specific capacity, excellent rate performance, and outstanding cycling stability when tested as cathode for aqueous lithium-ion batteries. It is found that the hydrothermally synthesized LiCoO2 sample without heat treatment still has some structure distortion with proton intercalation and Li + occupancy at abnormal sites, which deteriorate its electrochemical performance. By using the 3D hierarchy LiCoO2 nanorod arrays as cathode, a flexible aqueous LiCoO2 //LiTi2 (PO4 )3 lithium-ion battery device is successfully constructed, demonstrating superior rate performance and cycle performance. Graphical abstract: A confined dissolution-recrystallization synthesis route has been developed to grow the hierarchy layered LiCoO2 nanosheets assembled nanorod arrays on carbon cloth. The self-standing 3D cathode shows outstanding rate and cycle performance in the aqueous electrolyte. By using the 3D hierarchy LiCoO2 cathode, a flexible aqueous LiCoO2 //LiTi2 (PO4 )3 lithium-ion battery device is successfully constructed, demonstrating superior electrochemical performance and good flexibility. Highlights: A low-temperature synthesis is developed to grow hierarchy LiCoO2 nanorod arrays. Confined dissolution-recrystallization is applied for fabrication of 3D electrode. The self-standing 3D LiCoO2 cathode shows outstanding rate and cycle performance. A flexible aqueous LiCoO2 //LiTi2 (PO4 )3 LIB device is successfully fabricated.